2017
DOI: 10.7705/biomedica.v37i4.3432
|View full text |Cite
|
Sign up to set email alerts
|

Results of the national surveillance of antimicrobial resistance of Enterobacteriaceae and Gram negative bacilli in health care-associated infections in Colombia, 2012-2014

Abstract: Introducción. En el tercer trimestre de 2012, comenzó a operar el Sistema Nacional de Vigilancia de Resistencia Antimicrobiana en las infecciones asociadas a la atención en salud, con el fin de recabar y analizar la información referente al problema en Colombia.Objetivo. Describir los perfiles de resistencia y los resultados de la vigilancia por el laboratorio con base en los datos recolectados en el Sistema.Materiales y métodos. Se hizo un estudio descriptivo y retrospectivo con base en la información del Sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
4
17
0
9
Order By: Relevance
“…A previous study explored the knowledge, attitudes, and practices among 317 medical students in the United States, with the results indicating that 90% of the students desire more education on the appropriate use of antimicrobials, and only 33% perceived their preparedness to be adequate in some fundamental principles of antimicrobial use [13]. A survey in 13 European countries found large differences in teaching important principles on the prudent use of antibiotics [14], and another study in Congo, Africa found that knowledge regarding antibiotics was low [15]; however, in our country, despite antibiotic resistance being a substantial problem [16][17][18][19], no studies have described the reality of the training that primary antimicrobial prescribers have undergone.…”
Section: Introductionmentioning
confidence: 65%
“…A previous study explored the knowledge, attitudes, and practices among 317 medical students in the United States, with the results indicating that 90% of the students desire more education on the appropriate use of antimicrobials, and only 33% perceived their preparedness to be adequate in some fundamental principles of antimicrobial use [13]. A survey in 13 European countries found large differences in teaching important principles on the prudent use of antibiotics [14], and another study in Congo, Africa found that knowledge regarding antibiotics was low [15]; however, in our country, despite antibiotic resistance being a substantial problem [16][17][18][19], no studies have described the reality of the training that primary antimicrobial prescribers have undergone.…”
Section: Introductionmentioning
confidence: 65%
“…En 2014, un hospital reportó el incremento de cepas de Proteus mirabilis portadores del gen NDM, en 2016 otro hospital reportó el incremento de cepas de Klebsiella pneumoniae portadores del gen NDM, ambos reportes probablemente incrementaron los casos de enterobacterias portadoras del gen NDM (67,5 %) frente a KPC (31,3 %) y de IMP (1,2 %), esto es contrario a lo reportado por los sistemas de vigilancia de Colombia (20) , Chile (21) y Canadá (22) , donde KPC es la carbapenemasa más frecuentemente detectada en estos microorganismos.…”
Section: Discussionunclassified
“…When the modified HB&L® method for positive blood culture samples was compared with the conventional identification method, the presumptive positivity for the identification of carbapenemase-producing GNB was much faster when the modified HB&L was used (19 hours [18,22] vs. 61 hours [60, 64]; p < 0.001), including the positivity time from the Bact/Alert 3D® system. In other words, a 42-hour reduction was achieved in the early recognition of carbapenemase and/or oximino-cephalosporin resistance (Fig.…”
Section: Time To Identification Of Multi-drug Resistant Germsmentioning
confidence: 99%
“…Colombia was the first Latin American country to identify isolate producers of Klebsiella pneumoniae carbapenemases (KPC) [20] and the first country in the world to deliver isolates of KPC-producing Pseudomonas aeruginosa [21]. On top of that, the Colombian national epidemiological surveillance has detected an endemic circulation of various types of carbapenemases (OXA, NDM, and VIM) [22,23].…”
Section: Introductionmentioning
confidence: 99%